Phenotypic Characterization and Whole Genome Analysis of a Strong Biofilm-Forming Staphylococcus aureus Strain Associated With Subclinical Bovine Mastitis in Colombia - Torres, Giovanny; Vargas, Karen; Cuesta-Astroz, Yesid; Reyes-Vélez, Julián; Olivera-Angel, Martha (Frontiers in Veterinary Science, 2020)
Staphylococcus aureus represent a serious threat to public health due to food safety, antibiotic resistance, and the potential zoonotic transmission of strains between dairy cattle and humans. Biofilm formation by S. aureus results in chronicity of the infections which confers protection against the immune response and antibiotics. Likewise, biofilm allows the exchange of mobile genetic material among different strains through microbial interactions inside the matrix. In Colombia, where this pathogen continues to be one of the main isolated from bovine intramammary infections and milking by hand is highly frequent, there are knowledge gaps on the zoonotic potential of the strains. Therefore, the aim of this work was to characterize genotypically and phenotypically the S. aureus Sa1FB strain with strong biofilm production and to perform genomic and phenotypic comparisons with other relevant S. aureus strains (native and references strains). These results show a highly producer strain of biofilm and low ability of cell invasion compared to the other two native strains. In addition, high genomic similarity between S. aureus Sa1FB and the reference strains was observed, despite of the differences reported at the clinical level. However, Sa1FB exhibited special features in terms of mobile genetic elements, highlighting its ability to accept foreign genetic material. Indeed, this could increase mutation, pathogenesis and adaptability to new hosts, representing a risk for people in contact with the milk obtained from animals infected with these strains. These results present the relevance of surveillance for early detection of emergent clones with zoonotic potential, which allow to reduce the risk of occupational exposure and their spread in the community